3D printing technology for textiles and fashion. Issue 4 (1st October 2020) - Dip, Tanvir Mahady; Emu, Ayesha Siddika; Nafiz, Md Nafiul Hassan; Kundu, Puja; Rakhi, Hasnatur Rahman; Sayam, Abdullah; Akhtarujjman, Md; Shoaib, Mohammad; Ahmed, Md Shakil; Ushno, Swimi Tabassum; Asheque, Abdullah Ibn; Hasnat, Enamul; et al.
Abstract: 3D printing (3DP) is one of the modern approaches in the field of manufacturing. Although this process has been known for a fair amount of time, only the more-recent developments have revealed its potential for applications in different manufacturing sectors. Textiles, one of the basic human requirements, does more than just fulfilling the fundamental necessity of covering the body. Integrating 3DP technology in textiles has broadened the horizon of the textile world. This review explores the historical background as well as state-of-the-art developments in 3DP related to textiles and fashion. It discusses basic ideas about fundamental textile substrates, various 3DP technologies related to textiles, different printing devices and tools, materials used as print inks, direct printing of 3D objects on various textile substrates, fabrication techniques of 3D printed textile structures, different process parameters and their impacts, tests and standards, benefits and limitations. It also highlights the future for further implementation of 3DP technology in the textile industry. Overall, this issue of Textile Progress attempts to ascertain the potential of 3DP which, despite having some drawbacks, could enrich the outputs of the textile and fashion industry and motivate future designers and scientists to engage in its further exploration.